2014
DOI: 10.1016/j.bpj.2013.11.2960
|View full text |Cite
|
Sign up to set email alerts
|

Cutting the Wires: Modularization of Cellular Networks for Experimental Design

Abstract: Understanding naturally evolved cellular networks requires the consecutive identification and revision of the interactions between relevant molecular species. In this process, initially often simplified and incomplete networks are extended by integrating new reactions or whole subnetworks to increase consistency between model predictions and new measurement data. However, increased consistency with experimental data alone is not sufficient to show the existence of biomolecular interactions, because the interpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 41 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…2A and 5) that describes the directed information flow in a biomolecular network. In [23], we showed that…”
Section: Network Modularizationmentioning
confidence: 99%
See 3 more Smart Citations
“…2A and 5) that describes the directed information flow in a biomolecular network. In [23], we showed that…”
Section: Network Modularizationmentioning
confidence: 99%
“…, n M modules. Similar to our previous work [23], we require that each module contains exactly one output y m (t). Furthermore, each module's dynamics can depend on n M trajectories u(t) = (u 1 (t), .…”
Section: Network Modularizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of model decomposition, in contrast, is to partition a high-dimensional model into weakly connected modules, which can be analyzed by systems-theoretic methods [14]. Furthermore, the concept of modular subnetworks has been employed by other authors to discriminate between several possible networks (see, for example, [15], and references therein). Overall, this demonstrates that the relationship between realistic high-dimensional models and analyzable low-dimensional models is a highly present topic in systems biology.If this question of multistability equivalence could be answered, methods and results from systems analysis of low-dimensional systems and modeling via high-dimensional systems could be combined and thus greatly enhance the understanding of a particular GRN system at hand.…”
mentioning
confidence: 99%